2011
DOI: 10.1007/s00404-011-2037-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiotherapy on pain and functional activities after cesarean delivery

Abstract: Findings revealed the effectiveness of a physiotherapy program in the early post-cesarean period in a wider perspective than the current literature, and are considered to be valuable for increasing the quality and productivity of the postnatal care, therefore improving well-being after childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Although medications are safe for use by mothers post-CS, many females prefer non-pharmaceutical methods (16). A few studies on the advantages of nonpharmaceutical methods, including complementary and alternative medicine, have been conducted (17).…”
Section: Introductionmentioning
confidence: 99%
“…Although medications are safe for use by mothers post-CS, many females prefer non-pharmaceutical methods (16). A few studies on the advantages of nonpharmaceutical methods, including complementary and alternative medicine, have been conducted (17).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Although there are numerous studies in the literature investigating the relationship between various massage techniques and chronic constipation, the number of studies investigating the relationship between CTM and intestinal functions has been limited. 11,18 Holey and Lawler 11 investigated the effects of CTM and abdominal massage in a female patient with chronic constipation and found that both massage techniques improved the patient's defecation frequency and stool consistency, but CTM was found to be more effective. Karakaya et al 18 reported that CTM application on women who underwent cesarean delivery positively affected the bowel movement; moreover, gas passing and defecation, both of which indicate bowel movement, were experienced earlier in the CTM group compared with the control group.…”
Section: Discussionmentioning
confidence: 97%
“…Also, another study revealed that combination of pelvic exercises and CTM played a role in healing bowel functions in women immediately after cesarean delivery. 18 To the best of our knowledge, there currently is no randomized controlled trial investigating the effects of CTM on constipation. 19 Therefore, the present study aimed to examine the effects of CTM on the severity of constipation and on the QOL of individuals diagnosed with chronic constipation based on Rome III criteria.…”
mentioning
confidence: 99%
“…In a study of 50 women after cesarean delivery, ambulation was evaluated with pain intensity and analgesia requirements (Karakaya et al, 2012). The experimental group received physiotherapy with early mobilization.…”
Section: Benefits Of Early Postoperative Mobilizationmentioning
confidence: 99%